(untitled) (Jagannath University Journal of Arts, 2026)
The history of people power and politics in Bangladesh is intricately connected to the opposition protest movements dating back to the colonial era. Explanations abound on the glorification of history which are mainly imparted through autobiography and memoir. However, academic analysis of civilian protest movements in Bangladesh represents an important but little-known research area that this paper intends to address. The article is based on secondary sources, including published books and journals. Using historical analysis method, the paper finds that in all important juncture, the role of regular political elites–especially political party and leaders–became secondary, whereas the protest lead was taken over by the street masses who came from non-institutionalized political channels, ordinary village people, urban educated mass and socio-cultural networks, for example. The analysis suggests that the opposition movement in the Indian subcontinent era laid the foundation for the space of political contestation. It indicates that popular politics has grown out of the regular habits of Bengali people as an immediate response to regime oppression, social injustice and marginalized context. Jagannath University Journal of Arts, v-5, i-01, 2025: p193-203